2017
DOI: 10.1111/aji.12708
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal ratio of CD57+ cells to CD56+ cells in women with recurrent implantation failure

Abstract: Our study provides a novel assessment parameter, CD57+ cells to CD56+ cells ratio, to evaluate NK cells and its relation with Tregs in RIF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Recent studies have shown that peripheral blood and endometrial CD56 + cell and CD57 + cell concentrations of patients with RIF are significantly increased, and this increase is expected to become a new indicator for the evaluation of NK cells ( Jiang et al, 2017 ). In this study, we used an advanced method to measure the concentration of uNK cells and found that intrauterine perfusion of CsA significantly reduced the concentration of uNK cells and improved pregnancy outcomes among patients with RSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that peripheral blood and endometrial CD56 + cell and CD57 + cell concentrations of patients with RIF are significantly increased, and this increase is expected to become a new indicator for the evaluation of NK cells ( Jiang et al, 2017 ). In this study, we used an advanced method to measure the concentration of uNK cells and found that intrauterine perfusion of CsA significantly reduced the concentration of uNK cells and improved pregnancy outcomes among patients with RSA.…”
Section: Discussionmentioning
confidence: 99%
“…During the embeddedness phase, the endometrium sustains further embeddedness induced by chemokines and adhesion molecules, growth factors, cytokines and immune cells ( van Mourik et al, 2009 ). Additionally, uterine natural killer (uNK) cells, which are involved in alloimmunity, account for 65–70% of lymphocytes in the endometrium ( Jiang et al, 2017 ). Since 2018, our center has used low-molecular-weight heparin, aspirin, prednisone, lymphocyte immunotherapy for the husband and intravenous immunoglobulin (IVIG) to treat RSA patients.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Nevertheless, endometrial immune profiling by single-labeled IHC has been successfully used in identifying unfavorable pregnancy disorders, including RIF and RM. Dysregulated decidua CD68 + , CD86 + and CD163 + macrophages 20 and CD1a + , CD83 + DCs 37 in abortion and RM groups, and elevated ratio of endometrial CD57 + cells to CD56 + NK cells in RIF patients 24 were reported. Our group recently reported a pregnancy prediction model called 'EI-Score' , which consists of the frequency of endometrial CD68, CD163, and the embryo transfer strategy.…”
Section: Discussionmentioning
confidence: 93%
“…[17][18][19] It is postulated that dysregulation of immune cells may disrupt the dialogue between mother and fetus, leading to an unfavorable outcome, including implantation failure and miscarriage. [20][21][22][23][24] Implantation failure is distressing and needs to be urgently solved due to the cumulative mental burden imposed by pregnancy loss. Medical intervention was necessary, and ERA and immune profiling might benefit infertile couples.…”
Section: Introductionmentioning
confidence: 99%
“…Breakdown of maternal-fetal tolerance was found to be associated with a poor clinical outcome in pregnant women [8,9]. Furthermore, dysregulation of implicated immune cells such as uterine natural killer cells (NK), peripheral NK, regulatory T cells (Tregs), T-helper cells have been discovered in RIF [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%